2021 Comprehensive Surveillance Review : Background Paper on Main Findings from The Stakeholder Surveys. (Policy Papers; Policy Paper ;, 2021)
This note presents key results from the surveys of country authorities, IMF Executive Directors (EDs), and mission chiefs (MCs) to inform the Comprehensive Surveillance Review (CSR). Key takeaways and cross-cutting themes that emerge are Trends, Policy Challenges, Surveillance Priorities, Surveillance modalities and Traction.